Cardiac Metastasis in a Patient with Head and Neck Cancer: A Case Report and Review of the Literature - Joseph K. Kim; Kunal Sindhu; Richard L. Bakst (Case Reports in Otolaryngology)
Cardiac metastasis from a primary head and neck cancer is a rare finding. Most patients with cardiac metastases have nonspecific symptoms that may vary depending on the severity and location of the lesion. Due to the infrequency of reported cases, there are no clear guidelines for the diagnosis or management of cardiac metastasis in head and neck cancer patients. In this report, we discuss the case of a patient with a primary diagnosis of oral tongue cancer who developed a cardiac metastasis that was detected antemortem.